Factors Associated with Frequency of the First Permanent Molar Caries in Young Children of Multan District, Pakistan - Nazir, Amara; Asghar, Faisal; Akram, Sana; Haider, Ehsan; Rana, Sadiq Amin Ahmed; Khan, Muhammad Athar; Kashif, Muhammad (UI Scholars Hub, 2019)
Caries is the result of the interaction between tooth surface, microorganisms, and food. The first permanent molar (FPM) is known as the key tooth in the oral cavity and erupts around the age of 6 years. Objective: To determine the frequency of caries in the FPMs in young children and analyze factors associated with FPM caries. Methods: We recruited 350 subjects from different public and private sector schools of Multan District, Punjab, Pakistan, for this cross-sectional study. A predesigned questionnaire was used to collect data from eligible respondents. Dental caries status was assessed visually using a dental mirror, dental explorer, and light. Results: Of the 350 students, 108 were found to be affected with caries, whereas the remaining 242 were caries-free. Among the 108 affected students, 36 were male and 72 were female, and 80 were aged 7–9 years; the remaining 28 students were 10–12 years. Conclusion: Caries frequency varied by parent’s educational level, parent’s socioeconomic status, and also by the age and gender of the child.